Verbascum birjandense and V. urumiense (Scrophulariaceae), two new endemic species for Flora of Iran - Sotoodeh, Arash; Attar, Farideh; Laitung, Beryl; Civeyrel, Laure (Phytotaxa, 2022)
Verbascum birjandense and V. urumiense are described as new endemic species of Verbascum from eastern and northwestern Iran. It was not possible to assign the samples of these two taxa to any of the known Verbascum species in Iran and adjacent regions. Collating the morphological characters of the samples against the specialized and pertinent literature of the genus led us to propose them as new species. Both belong to section Bothrosperma, subsection Fasciculata.                These new species are morphologically close to V. erianthum and V. songaricum based on some key characteristics, but show some differences in basal leaves shape, pedicel size, the ratio of pedicel to calyx, presence of hairs inside the corolla, and the hair color of the stamen’s filaments. Distribution map and details of important characters are also presented.